Stabilisasi Dan Kemungkinan Penggunaan Kembali (Reuse) Lumpur B3 Industri Elektroplating - Dwinna Rahmi (Jurnal Kimia dan Kemasan, 2000)
Sludge from waste water treatment of electroplating industry contains hazardous waste. Before sludge is dumped to landfill it's need treatment to reduce hazard matter. One of general treatment is sludge stabilization by adding cement and sand to get concrete block. From these research shows that sand is playing important role in binding heavy metal in cement. The mixing between sand, cement and sludge I: I: 2 as per standard for landfill (PP. no 85, 1999) can stabilized sludge but can not reuse as a building material because still contains heavy metal.